In Silico Study of Chemical Compounds from Jamblang (Syzygium Cumini) Targeting the PERK Receptor as Leukemia Candidate Agents: Studi In Silico Senyawa Kimia Tanaman Jamblang (Syzygium Cumini) Terhadap Reseptor PERK Sebagai Kandidat Obat Leukemia - Al Attarsyach; Adelina, Rosalin Teisya; Supandi (Jurnal Riseta Naturafarm, 2026)
Indonesia’s floral biodiversity provides significant opportunities for researchers to explore secondary metabolites as potential candidates for novel anticancer drugs, particularly for blood cancer (leukemia). This study aimed to analyze the chemical constituents of jamblang (Syzygium cumini) that exhibit favorable potential and conformations as leukemia agents targeting the PERK receptor. The method employed was an in-silico study based on molecular docking using AutoDock Tools, followed by visualization with BIOVIA Discovery Studio Visualizer, as well as pharmacokinetic and toxicity (ADMET) analyses using pkCSM. The molecular docking results demonstrated that Lycopene was the best-performing test ligand, exhibiting the lowest binding energy ΔGbind value of −12.34 kcal/mol. In addition, one test ligand, Myricetin-3-O-rhamnoside, showed potential as a biomarker compound with a ΔGbind value of −8.02 kcal/mol and may be utilized for further research. Meanwhile, the native ligand GSK2606414, used as the positive control, showed a ΔGbind value of −12.11 kcal/mol. Pharmacokinetic and toxicity studies were conducted on the best-performing test ligands obtained from the molecular docking analysis. Based on the ADMET analysis, six test ligands exhibited the most favorable pharmacokinetic and toxicity profiles. Therefore, it can be concluded that jamblang (Syzygium cumini) has promising potential as a source of anticancer agents for leukemia.